Clinical Relevance of PD-L1 Expression and CD8+ T Cells’ Infiltration in Patients With Lung Invasive Mucinous Adenocarcinoma - Xu, Xiaoling; Li, Na; Wang, Ding; Chen, Wei; Fan, Yun (Frontiers in Oncology, 2021)
Background: Invasive mucinous adenocarcinoma (IMA) of lung is a rare and distinct subtype of adenocarcinomas. At present, people have no ideals whether IMA patients can benefit from immunotherapy and target therapy, thus there is an urgent need to clarify the immune microenvironment and genetic characteristics of this cohort. Methods: A total of 31 IMA patients matched with 27 non-mucinous adenocarcinoma (non-IMA) patients were enrolled in this study, and clinical data was collected. Immunohistochemistry was used to determine the expression of PD-L1, the abundance of CD8+ tumor-infiltrating lymphocytes (TILs), and the mutations of ALK. And PCR was used to determine the mutations of EGFR. The Chi-square test, Cox proportional hazard regression model and Kaplan-Meier method were used to explore the correlations between these clinicopathological variables, survival and identify risk factors. Results: 9.7% (3/31) of the IMA patients showed positive PD-L1 expression and 35.5% (11/31) showed CD8+ TIL infiltration, which were markedly lower than that of non-IMA group (PD-L1: 48.1% [13/27]; CD8: 81.5% [22/27]). Moreover, 5 (16.1%) patients in IMA group and 10 (37.0%) patients in non-IMA group had EGFR mutations, and 9 (29.0%) patients in IMA group and 0 (0.0%) patient in non-IMA group had ALK rearrangements. Additionally, we observed that IMA patients with CD8+ TIL infiltration had a worse prognosis than CD8-negative group (P = 0.024). And multivariate analyses showed that CD8 was an independent prognostic factor for patient survival (HR = 5.60, 95 % CI: 1.35–23.22, P = 0.017). Conclusion: Patients with IMA have lower levels of PD-L1 expression and CD8+ TIL infiltration in tumor microenvironment, and also have a lower frequency of EGFR mutations and a higher frequency of ALK rearrangements than non-IMA patients. Our results provide important reference for therapy of lung IMA.